Nursing care for children with special health care needs in primary care - Machado, Marília Girão de Oliveira; Ferreira, Ariédna da Hora; Mota, Francisca Rosana Gonçalves; Ribeiro, Laisa Maria dos Santos; Bezerra, Gabriela Sabatine Ribeiro; Alencar, Delmo de Carvalho; Ibiapina, Aline Raquel de Sousa (Revista de Enfermagem da UFPI, 2022)
Objective: To analyze, based on scientific evidence, nursing care for children with special health care needs in Primary Health Care. Methods: Integrative literature review, with search and selection in MEDLINE databases via PubMed®, LILACS, Embase, SCOPUS and in the Scielo electronic library. Ten primary studies were included, available in full, published between 2011 and 2021, in English, Portuguese and Spanish. Results: Despite the great need for technical knowledge in assisting CSHCN, it is evident the need for these children and their families to be attended in full, and not just with biomedical approaches that limit nursing care in terms of identifying aspects related to the clinical picture of these children. It was also evidenced that nurses, for the most part, do not feel prepared to provide adequate care due to the complexity of the health conditions, the deficiency in professional training or the lack of periodic and specific training after graduation. Conclusion: Nursing care in the care for CSHCN happens in a fragmented way and with actions based on the biomedical model. The findings showed little access and inclusion, in addition to a shortage in the provision of training for nurses as a frequent problem in primary care.